2010
DOI: 10.1007/s10532-010-9444-y
|View full text |Cite
|
Sign up to set email alerts
|

Cometabolic biotransformation of fenpropathrin by Clostridium species strain ZP3

Abstract: A novel bacterial strain capable of degrading the pyrethroid pesticide fenpropathrin was isolated from mixed wastewater and sludge samples. Phylogenetic analysis of the 16S rDNA sequence revealed that the organism belongs to the genus Clostridium. The organism can co-metabolically transform fenpropathrin at 100 mg l(-1) at 35°C and pH 7.5 in 12 days. Metabolic products of fenpropathrin from strain ZP3 were examined by gas chromatography/mass spectrometry, and the results showed that the organism degraded fenpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…This result was different from that of Clostridium sp. ZP3, which exhibits high efficiency in degrading fenpropathrin in the presence of glucose (Zhang et al, 2011). Although the plant exudates and extracts can offer several bioavailable substrates, their relatively smaller concentrations lead to a less significant increase in bacterial growth and degradation of fenpropathrin, as expected.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This result was different from that of Clostridium sp. ZP3, which exhibits high efficiency in degrading fenpropathrin in the presence of glucose (Zhang et al, 2011). Although the plant exudates and extracts can offer several bioavailable substrates, their relatively smaller concentrations lead to a less significant increase in bacterial growth and degradation of fenpropathrin, as expected.…”
Section: Discussionmentioning
confidence: 51%
“…The bacterial growth was monitored by measuring the absorbance at OD 600 by a spectrophotometer (UV-1700; Shimadzu). Fenpropathrin residuals in the water phase were extracted and quantified as per the method of Zhang et al (2011) with a slight modification. Briefly, the water phase was extracted twice with an equal volume of dichloromethane.…”
Section: Bacterial Growth and Fenpropathrin Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, the isolate experienced a prolonged slow growth phase for utilizing fenpropathrin at higher initial concentrations (over 100 mg l -1 ), but was not completely inhibited even at concentration as high as 800 mg l -1 . However, studies in the past reported that the fenpropathrin-degrading strains usually transform the pesticides with concentration lower than 200 mg l -1 [4,34]. This feature gives the isolate a competitive advantage in diverse environments, especially exposed to a high concentration of fenpropathrin pollution.…”
Section: Effect Of Different Initial Fenpropathrin Concentrations On mentioning
confidence: 99%
“…To date, a few fenpropathrin-degrading microorganisms such as Sphingobium cloacae [4], Clostridium celerecrescens [34], Ochrobactrum tritici [31], and Haihai Song and Zhiren Zhou have equally contributed to this work.…”
Section: Introductionmentioning
confidence: 99%